Encapsulation of Cardiac Stem Cells to Enhance Cell Retention and Cardiac Repair - Mayfield, Audrey (Université d'Ottawa / University of Ottawa, 2014)
Despite advances in treatment, heart failure remains one of the top killers in Canada. This recognition motivates a new research focus to harness the fundamental repair properties of the human heart, with human cardiac stem cells (CSCs) emerging as a promising cell candidate to regenerate damaged myocardium. The rationale of this approach is simple with ex vivo amplification of CSCs from clinical grade biopsies, followed by delivery to areas of injury, where they engraft and regenerate the heart. Currently, outcomes are limited by modest engraftment and poor long-term survival of the injected CSCs due to on-going cell loss during transplantation. As such, we explored the effect of cell encapsulation to increase CSC engraftment and survival after myocardial injection. Transcript and protein profiling of human atrial appendage sourced CSCs revealed strong expression the pro-survival integrin dimers αVβ3 and α5β1- thus rationalizing the integration of fibronectin and fibrinogen into a supportive intra-capsular matrix. Encapsulation maintained CSC viability and expression of pro-survival transcripts when compared to standard suspended CSCs. Media conditioned by encapsulated CSCs demonstrated superior production of pro-angiogenic/ cardioprotective cytokines, angiogenesis and recruitment of circulating angiogenic cells. Intra-myocardial injection of encapsulated CSCs after experimental myocardial infarction favorably affected long-term retention of CSCs, reduced scar burden and improved overall cardiac function. Taken together, cell encapsulation of CSCs prevents detachment induced cell death while boosting the mechanical retention of CSCs to enhance repair of damaged myocardium.
Keywords: Cardiac stem cell; Encapsulation; Myocardial infarction; Biomaterials